Development of Drought Tolerant Rice Variety BRRI dhan66 for Rainfed Lowland Ecosystem of Bangladesh (Bangladesh Rice Journal, 2020)
A newly released drought tolerant rice variety BRRI dhan66 suitable for rainfed lowland ecosystem of Bangladesh is an improvement over existing drought tolerant rice varieties. The variety has satisfactorily been passed in the proposed variety trial conducted in the farmers’ field. As a result, National Seed Board (NSB) approved this variety for commercial cultivation in the wet season (T. Aman) in 2014. It has modern plant type with 120 cm plant height and matures in 110-115 days. The important feature of this variety is higher drought tolerance during reproductive stage. It can produce 4.5-5.0 t/ha grain yield without irrigation during reproductive stage. It can produce satisfactory yield when soil moisture remains